2014
DOI: 10.1002/jbmr.2277
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of CD26 Signaling Inhibits Human Osteoclast Development

Abstract: Bone remodeling is maintained by the delicate balance between osteoblasts (OBs) and osteoclasts (OCs). However, the role of CD26 in regulating bone remodeling has not yet been characterized. We herein show that CD26 is preferentially expressed on normal human OCs and is intensely expressed on activated human OCs in osteolytic bone alterations. Macrophage-colony stimulating factor (M-CSF) and soluble receptor activator of NF-kB ligand (sRANKL) induced human OC differentiation, in association with CD26 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 52 publications
1
32
1
Order By: Relevance
“…Soluble DPP4 levels have previously been demonstrated to be increased in postmenopausal women, consistent temporally with the higher rates of bone remodeling that occur following menopause 25 . In agreement with our findings, a previous report demonstrated expression of the membrane-bound form of DPP4, CD26, on osteoclasts in human bone in normal and pathological conditions 29 . As DPP4 is a peptidase targeting glycine/proline sequences, it is possible that osteoclast-derived DPP4 contributes to the degradation of collagen 30 .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Soluble DPP4 levels have previously been demonstrated to be increased in postmenopausal women, consistent temporally with the higher rates of bone remodeling that occur following menopause 25 . In agreement with our findings, a previous report demonstrated expression of the membrane-bound form of DPP4, CD26, on osteoclasts in human bone in normal and pathological conditions 29 . As DPP4 is a peptidase targeting glycine/proline sequences, it is possible that osteoclast-derived DPP4 contributes to the degradation of collagen 30 .…”
Section: Discussionsupporting
confidence: 94%
“…As DPP4 is a peptidase targeting glycine/proline sequences, it is possible that osteoclast-derived DPP4 contributes to the degradation of collagen 30 . However, inhibition of the membrane-bound form of DPP4 appeared to inhibit osteoclast differentiation in vitro without affecting osteoclast resorptive activity 29 . Treatment of osteoblast cultures or mice with DPP4 inhibitors improved osteogenic differentiation and fracture healing 31 .…”
Section: Discussionmentioning
confidence: 97%
“…DPP4 is also known Cluster of differentiation 26 (CD 26). Recent study showed that inhibition of CD 26 signaling inhibited human osteoclast development and humanized anti-CD26 monoclonal antibody may have therapeutic potential for the treatment of osteolytic lesions [33]. Recently some studies reported that DPP4i had anti-inflammatory effects and it also becomes the another possibility [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that the blockade of CD26 (DPP-4) signaling inhibits the p38 MAPK phosphorylation pathway, which is known to be an important step in early human osteoclast differentiation, and consequently impairs the development of human functional osteoclasts (Nishida et al, 2012, 2014). However, researchers examined the efficacy of thevidagliptin and found no significant inhibitory effect on human osteoclast differentiation or maturation.…”
Section: Potential Mechanisms Of Dpp-4is On Bone Metabolismmentioning
confidence: 99%